TITLE THE DIFFERENCES BETWEEN MACHINE TRANSLATION AND HUMAN TRANSLATION: ADVANTAGES AND LIMITATIONS (KONFERENSIYA, 2025)
this abstract presents a brief summary of the main theme: the difference in objectives, approach, quality, and effect of machine translation and human translation. It will also touch upon the benefits of both and the developing applications of the emerging concept of hybrid models involving Computer-Aided Translation tools and post-editing of MT.